Metrics from a Congenital Hypothyroidism Screening Program – A Tale of Unmet Challenges - Kanani, Fatima; Kumar, Vikram; Mushtaq, Mamona; Sameer, Dua; Ali, Rehan (Journal of Maternal and Child Health, 2025)
Background: Congenital hypothyroidism is one of the most common Inherited Metabolic Diseases for which newborn screening is recommended. A wide-scale program for this is lacking in our country. We undertook a study to retrospectively review our metrics from a regional project for newborn screening of Congenital Hypothyroidism including frequency of elevated neonatal Thyroid Stimulating Hormone (TSH), recall rate, rate of missed testing and turnaround time for results. Subjects and Method: Retrospective data of neonates born between 13th July 2020 and 10th August 2021 was collected from electronic medical records. Dried blood spot specimens for TSH were collected from the umbilical cords for neonates born vaginally and by heel prick for those born by caesarian section and sent to the designated laboratory. Data was entered on Microsoft Excel and analyzed. Results: 4037 babies were screened for neonatal TSH, 2149 males and 1888 females. The median (IQR) TSH level was 3.34 (2.09-5.30) µIU/mL. The TSH levels of ≥15 µIU/mL were noted in 95 newborns, out of which 31 newborns had values of ≥ 20 µIU/mL. There was a median (IQR) turnaround time of 14.00 (4.00-55.00) days for initial results accessibility to the clinician. The recall rate was 0.3%. Around 10% of the neonates were not screened and retesting was performed in 12 neonates with high TSH. Only one neonate was identified with persistently raised TSH and suppressed FT4. Conclusion: Congenital Hypothyroidism was diagnosed in one out of 4037 neonates while 10% were not screened. Recall rate was low, 0.3%. The median turnaround time for reporting was 14 days. Increased awareness, strict monitoring, resource allocation, administrative support and follow-up are required for successful implementation of a CH screening program.